Penilaian Kondisi Permukaan Jalan Metode Pavement Condition Index (PCI) pada Ruas Jalan Kapten Piere Tendean Kota Tegal - Nurrohman, Hafidz; Hadi, Suprapto (Universitas Ibn Khaldun, 2026)
Roads have a crucial role in supporting mobility movement and allocation of goods and services, significantly impacting economic, social, and cultural growth. Damaged road conditions can impade activities and increase the risk of accidents. Road safety is influenced by various factors, including the road itself. Kapten Piere Tendean Street, part of the North Ring Road, is one of the vital routes is currently experiencing various types of damage, partly due to the increasing traffic volume. This papper aims to evaluate the surface condition of Kapten Piere Tendean street using the Pavement Condition Index (PCI) method for identify categories and levels of road damage as a basis for repair recommendations. The identification results show 13 types of damage, with the highest being shoving at 36%. At STA 0+00 – 0+100, the PCI score is 7, categorized as failed, while at STA 1+300 – 1+400, the PCI score is 92, categorized as excellent, with 32% of segments classified as very good. The average PCI score for the 2.9 km road length is 61, indicating the road is in good condition. The repair recommendations refer to Bina Marga guidelines, addressing the largest damage (shoving) with pothole patching (P5) and leveling (P6).